Physical tourism potentials in Mubi Town, Adamawa State, Nigeria - Abdullahi, Hashim; Asmawi, M. Zainora; Abdul Aziz, Abdul Razak (Kulliyah of Architecture and Enviromental Design, 2018)
World tourism is the fastest growing industries in the world that among others provides multi-million jobs opportunities; assisting in the significant infrastructure development and cross-cultural appreciations. It also supports revenue generation to governments at all levels and serves as the most contributing sector to many countries of the world. Thus, this paper carries out an empirical investigation of the physical tourism potentials of Mubi Town, Adamawa State, Nigeria. Primary data was collected through a well-structured questionnaire survey using five grading scale, and site observations of the physical tourism potentials. A total of 100 residents were selected as the respondents via random sampling technique. The research discovered six significant physical tourism potentials out of 12, namely; Tike Cattle Market, Wednesday Market, traditional local industries, Emir Palace, two minarets of Central Mosque, and River Yadzram. The analysis for the reliability test was also carried out using Spearman correlation techniques between the various segments of the questionnaire. This is based on the respondents’ responses to ascertain the level of the reliability. The descriptive statistics were used to correlate the relationship between Physical Tourism Potentials (PTP) and Environmental Elements (EE) of the study area. The result demonstrates the correlation between PTP and EE is highly significant at (0.01, 2-Tailed), indicating that, the Physical Tourism Potentials (PTP) in Mubi Town plays an integral role in the tourism potentials of the town.